2007
DOI: 10.1071/ah070603
|View full text |Cite
|
Sign up to set email alerts
|

Building an evidence base for community health: a review of the quality of program evaluations

Abstract: An assessment of the quality of program evaluations conducted in South Australian community health services investigated how effective evaluation reporting is in producing an evidence base for community health. Evaluation reports were assessed by a team of reviewers. Practitioner workshops allowed an understanding of the uses of evaluation and what promotes or acts as a barrier to undertaking evaluations.Community health services do undertake a good deal of evaluation. However, reports were not generally expli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 10 publications
0
20
0
Order By: Relevance
“…In contrast, experimental designs can be difficult to implement, an observation Smith and colleagues make in their review of quantitative methods used in Australian health promotion research. 27 It is possible that evaluations examined in this study may have been inadequately funded and underresourced in terms of evaluation time, staff time, and support, which commonly occurs in health promotion, 13,18,20,28 leading to the selection of a more convenient design. The same reasons may explain why surveys were the most common data collection method.…”
Section: Research Measuresmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, experimental designs can be difficult to implement, an observation Smith and colleagues make in their review of quantitative methods used in Australian health promotion research. 27 It is possible that evaluations examined in this study may have been inadequately funded and underresourced in terms of evaluation time, staff time, and support, which commonly occurs in health promotion, 13,18,20,28 leading to the selection of a more convenient design. The same reasons may explain why surveys were the most common data collection method.…”
Section: Research Measuresmentioning
confidence: 99%
“…10,11 In addition, credible evaluations increase respect for health promotion. 12 However, health promotion interventions often are not well evaluated 13,14 and, in some cases, not evaluated at all. 6,15 Inconsistent health promotion evaluation occurs for a range of reasons.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the fundamental importance of these principles, they seldom feature in evaluation reporting. 3,4 A review of 93 evaluations conducted in South Australian (SA) metropolitan community health services found that, although there is considerable…”
Section: Introductionmentioning
confidence: 99%
“…Equity of access to services and in health outcomes are key goals of Primary Health Care (PHC) (World Health Organization, 1978) A review of PHC service evaluations in South Australia (Jolley et al, 2007) found that although equity was a central concern of PHC services it was seldom explicitly evaluated. Additionally, PHC evaluations largely focus on only single programs rather than the whole of the service (Hurley et al, 2010).…”
Section: Introductionmentioning
confidence: 99%